Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Influence of graphene oxide on the toxicity of polystyrene nanoplastics to the marine microalgae Picochlorum sp. - Gamze Yesilay; Layla Hazeem; Mohamed Bououdina; Demet Cetin; Zekiye Suludere; Alexandre Barras; Rabah Boukherroub (Environmental Science and Pollution Research, 2022)

Anti-biofilm activity of dodecyltrimethylammonium chloride microcapsules against Salmonella enterica serovar Enteritidis and Staphylococcus aureus - Simon Khelissa; Adem Gharsallaoui; Jian Wang; Emilie Dumas; Alexandre Barras; Charafeddine Jama; Fouzia Jbilou; Noureddine Loukili; Nour-Eddine Chihib (Biofouling, 2021)

Toxicity effect of graphene oxide on growth and photosynthetic pigment of the marine alga Picochlorum sp. during different growth stages - Layla J. Hazeem; Mohamed Bououdina; Etienne Dewailly; Christian Slomianny; Alexandre Barras; Yannick Coffinier; Sabine Szunerits; Rabah Boukherroub (Environmental Science and Pollution Research, 2017)

Synoptic climatology of extreme precipitation in alpine Australia - Sonya Louise Fiddes; Alexandre Bernardes Pezza; Vaughan Barras (International Journal of Climatology, 2015)
Extreme precipitation over the eastern Australia can be significantly enhanced by topographic interaction with the westerly flow. These extreme events can cause severe flooding, damage and disruption to human activities, yet in some areas they are also an invaluable source of water and snow. In this study, we use rain gauge and snowfall accumulation data to investigate connections between extreme rain and snow in alpine Australia and the large‐scale climate. These data have been divided into three geographical locations: the west of the mountains, the ridgeline and the east of the mountains in order to explore the nature of precipitation in each region. The results confirm previous synoptic patterns found earlier in the literature for the western slopes (namely embedded and cutoff lows), and add new insights into the different processes conducive to extreme precipitation on the eastern side of the ranges, which we find to be mostly associated with a blocking structure connected to polar latitudes. Interestingly, our analyses suggests that while a La Niña pattern accompanied by enhanced meridional sea surface temperature ( SST ) gradients over mid‐latitudes is associated with extreme events in the western and high regions, the extreme precipitation composites for the eastern region are associated with a SST pattern that resembles the predominant signal associated with global warming in the Australian region. We hypothesize that while the western and high regions rely on SST gradients, which enhance the westerly jet, the extreme events over the eastern side rely on blocking patterns (anomalous easterlies), which are at least partially responding to the global SST warming with the respective shift of the westerlies to the south. These results help explain why the precipitation over the western side of the Alps is declining more rapidly than the total precipitation observed on the eastern side.

A new ‘bio-comfort’ perspective for Melbourne based on heat stress, air pollution and pollen - Stephanie J. Jacobs; Alexandre B. Pezza; Vaughan Barras; John Bye (International Journal of Biometeorology, 2014)